Life-threatening DBS withdrawal syndrome in Parkinson's disease can be treated with early reimplantation. (November 2018) - Reuter, S.; Deuschl, G.; Berg, D.; Helmers, A.; Falk, D.; Witt, K.
Abstract: Introduction: The deep brain stimulation (DBS) withdrawal syndrome (DBS-WDS) is a rare, life-threatening complication in Parkinson's disease (PD) patients with long disease duration and stimulation when stimulation is terminated for extended periods mostly due to infection of the DBS-hardware. Methods, results: In five patients explantation became necessary because of infection after a mean of 11.4 years (range 4–15 years) of DBS and a mean disease duration of 24.6 years (range 3–22 years). Mean UPDRS motor-score pre-explantation was 38 points (range 24–55 points) which increased to a mean of 78.4 points (range 58–90 points) after explantation, despite optimal Levodopa dosing. Reimplantation of the hardware after 23 days (range 3–45 days) under antibiotic treatment led to an improvement to a mean of 40 points (range 25–73 points) and a complication free survival. Conclusion: Early reimplantation of the DBS-hardware is a treatment option of the DBS-WDS when the life-threatening urgency overrides surgical standards. Observation of the syndrome indicates pharmacological unresponsiveness of the dopaminergic system in advanced PD and long-term DBS. Highlights: After removal of DBS in Parkinson's disease a life-threatening withdrawal can occur. The Severe akinetic state during withdrawal does not respond tol -Dopa. The life-threatening situation can be treated by early reimplantation of DBS. Despite an increased risk, no reinfections were found after early reimplantation. After early reimplantation of DBS all patient with a DBS withdrawal syndrome survived.